The Role of Dose-Dense Neo Adjuvant Triple H Therapy, Hugs, Humor and Humility: Palliative Medicine, Oncology, and the Human Spirit – A Clinician’s Journey - Doron Feinsilber (Palliative Medicine and Hospice Care, 2015)
The road to becoming a medical oncologist is a unique lattice of spiritual academic stamina. The roots of my academic and spiritual journey began well into my childhood when I was raised in a kind, warm, and genuine family. My mother and father, both immigrants who came from Israel with hardly a formal education or command of the English language came to the United States to provide a greater life for the next generation.